Effect of Outstanding Credit Volume, Loan to Deposite Ratio, Loan Interst Rate On Credit Union Return On Assets In Indonesia - Sabinus Beni; Windhu Putra; Nurul Bariyah (Journal of Economic and Business Analysis, 2023)
This study aimed to analyze the factors that affect Non-Performing Loan (NPL) risk in credit unions and factors that affect Return On Assets (ROA) in cooperatives. The study found that credit unions could minimize NPL risk by utilizing social networks according to the theory of social capital, and by ensuring that management and members share the same goals in managing credit risk according to the agency theory. The microfinance theory suggests that credit unions should provide appropriate financing. Multiple linear regression analysis indicated a significant influence of Loan to Deposit Ratio and Loan Interest Rate on ROA. Thus, credit unions should consider the use of deposit funds and set appropriate interest rates to increase ROA and strengthen member relationships. In managing credit risk, credit unions can utilize the theories of social capital, agency, and microfinance.